2010
DOI: 10.1186/1757-7241-18-48
|View full text |Cite
|
Sign up to set email alerts
|

Early identification and delay to treatment in myocardial infarction and stroke: differences and similarities

Abstract: BackgroundThe two major complications of atherosclerosis are acute myocardial infarction (AMI) and acute ischemic stroke. Both are life-threatening conditions characterised by the abrupt cessation of blood flow to respective organs, resulting in an infarction. Depending on the extent of the infarction, loss of organ function varies considerably.In both conditions, it is possible to limit the extent of infarction with early intervention. In both conditions, minutes count.This article aims to describe difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 217 publications
(209 reference statements)
3
52
0
3
Order By: Relevance
“…11 The results are however in accordance with Kim et al who also did not find any association of prehospital delay with age or sex. [12] Elderly population living alone in developed countries like Japan is also at a greater risk of prehospital delay such as described by Yanagida T et al [7]No such factor was found in our study as a cause in our population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…11 The results are however in accordance with Kim et al who also did not find any association of prehospital delay with age or sex. [12] Elderly population living alone in developed countries like Japan is also at a greater risk of prehospital delay such as described by Yanagida T et al [7]No such factor was found in our study as a cause in our population.…”
Section: Discussionsupporting
confidence: 80%
“…[5] In a previous study history of previous stroke has been implicated as a factor in shorter delay while accompanied diabetes has been associated with a longer delay of hospital arrival in patients with diabetes. [11] We however admit the limitation of study not to have recorded such history in all of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, current Australian and American College of Cardiology and American Heart Association (ACC/AHA) guidelines for the treatment of ST-segment elevation myocardial infarction (STEMI) recommend the time from first medical contact to percutaneous coronary intervention (PCI) to be as-soon-as-possible 4 or less than 90 minutes, 5,6 with suggestions that EMS to PCI time should be less than 90 minutes as well. 5,7 Many studies have investigated reasons for underuse of emergency ambulances 8,9 and delay in seeking treatment 10,11 in MI patients. Research has shown that pre-hospital median delays range from 84 to over 400 minutes.…”
Section: Current Guidelinesmentioning
confidence: 99%
“…Other studies reveal that patient delays were associated with sex (women had longer PHDs, as they took longer time to make decisions), ethnicity (an increased PHD, in the case of AMI, was found among the Asian and Latino populations in the USA), indecisiveness, fear, atypical presentation, lack of information, misinterpretation, reluctance to call a physician, lack of encouragement, and having a medical history and depression. [15][16][17] PHDs were further exacerbated when patients sought treatment at an intermediate care facility, which may not be equipped to deal with cardiac emergencies. The total mean travel times to arrive at, stay in an intermediate health institution, and subsequently arrive at the hospital were 0.5, 4.1, and 1.2 hours, respectively.…”
Section: Discussionmentioning
confidence: 99%